The increase in efficiency of milling of small-sized grooves of shaped form in hard-to-reach places of molds for rubber-technical products - I. N. Drozdov; A. Yu. Popov (Омский научный вестник)
This article discusses the methods of processing gas exhaust grooves on molds for rubber goods planning on a curved surface. The purpose of this work is to improve the efficiency of processing gas-venting grooves of angular shape on molds for rubber technical products on curved surfaces by using the planning method on machines with computer numerical control.